Evaluation of treatment modalities for congenital ptosis: indications, techniques, and long-term outcomes - Qadir, Afza; Ullah, Naz; Khan, Aleena; Ashraf, Muhammad; Hussain, Noor Ul (International Journal of Pathology, 2025)
Background: Congenital ptosis, characterized by drooping of the upper eyelid present at birth, can adversely affect visual development and facial appearance. Timely surgical correction is essential to prevent amblyopia, maintain a clear visual axis, and achieve satisfactory functional and cosmetic outcomes. Our objective is to evaluate the indications, surgical procedure, and results of different methods of surgery in congenital ptosis on long-term follow-up. Methods: This Prospective observational study was carried out over a span of 4 years, January 2021 to December 2024), in Ophthalmology department, Hayatabad Medical Complex, Peshawar. This study included 38 patients aged 3 to 18 years with simple congenital ptosis. Preoperative assessment included the levator function, MRD1, the palpebral fissure height, Bell’s phenomenon, and visual acuity. The patients underwent frontalis suspension, levator resection, and/or conjoint fascial sheath (CFS) sling according to levator function and ptosis degree. Results: In the preoperative period, the average MRD 1 was 0.7 ± 0.5 mm and it was significantly increased to 3.1 ± 0.6 mm postoperatively (p < 0.001). Frontalis suspension was carried out in 24 patients, levator resection in 15, and CFS suspension in 5. Overall, 86.4% of patients had eyelids (≤1 mm asymmetry), and the best results were found in the CFS group. Recurrence was observed in 9.1%, predominantly in the frontalis suspension group. Lagophthalmos was observed in 25% of subjects, with predominance of mild forms. Conclusion: Conjoint fascial sheath suspension with or without levator advancement is a safe and effective, less morbid approximation to frontalis suspension in certain types of congenital ptosis, particularly in patients with fair to good levator function. It results in improved eyelid symmetry, less complications and better patient satisfaction.